Production of building elements based on alkali-activated red clay brick waste - Robayo-Salazar, Rafael Andres; Mejía de Gutiérrez, Ruby; Mulford-Carvajal, Alexandra Jimena (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper analyzes the feasibility of reusing a red clay brick waste (RCBW) in order to produce building elements such as blocks, pavers and tiles, by using the technique of alkaline activation. The production of these building elements was based on the design of a hybrid mortar with 48.61 MPa of compressive strength, at 28 curing days at room temperature (25 °C). The hybrid mortar was synthesized by adding 10% by weight of Portland cement (OPC) to the RCBW, Red Clay Brick Waste. As alkaline activators were used commercial industrial grade sodium hydroxide (NaOH) and sodium silicate (Na2SiO3). Building elements were physically and mechanically characterized, according to Colombian Technical Standards (NTC). This technology process is presented as an alternative for the reuse of RCBW and its contribution to the environmental sustainability.